2020
DOI: 10.1002/adhm.201901435
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Biomaterials and Processing Methods for Liver Regeneration: State‐of‐the‐Art and Future Trends

Abstract: Liver diseases contribute markedly to the global burden of mortality and disease. The limited organ disposal for orthotopic liver transplantation results in a continuing need for alternative strategies. Over the past years, important progress has been made in the field of tissue engineering (TE). Many of the early trials to improve the development of an engineered tissue construct are based on seeding cells onto biomaterial scaffolds. Nowadays, several TE approaches have been developed and are applied to one v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 264 publications
(305 reference statements)
0
23
0
Order By: Relevance
“…These scaffold revealed similar structures and possessed mechanical properties of native liver tissue, indicating that it can be used as a liver substitute when liver donation is not feasible. 143,144 Uygun et al used an antegrade perfusion method to develop the first de-cellularized whole-organ rodent liver and obtained a translucent acellular tissue within few days. 145 Successful decellularization of a human liver was performed using a novel retrograde, two-step, perfusion methodology.…”
Section: 31) Extracellular Matrix -mentioning
confidence: 99%
“…These scaffold revealed similar structures and possessed mechanical properties of native liver tissue, indicating that it can be used as a liver substitute when liver donation is not feasible. 143,144 Uygun et al used an antegrade perfusion method to develop the first de-cellularized whole-organ rodent liver and obtained a translucent acellular tissue within few days. 145 Successful decellularization of a human liver was performed using a novel retrograde, two-step, perfusion methodology.…”
Section: 31) Extracellular Matrix -mentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are widely studied in the fields of immunology and regenerative medicine because of their wide sources, easy access, immune regulatory role, and promotive effect on tissue regeneration 3 , 4 . Previous studies have shown that MSCs have an important role in immunoregulation and tissue repair by interacting with inflammatory cells 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, these materials allow gas and mass transport, water retention, physical support, and physical cell aligning [32,33]. However, conventional polymers present a variety of disadvantages to novel technologies such as the use of organoids [34,35], whole-organ engineering [36,37], patient-specific tissue regeneration [38], and in situ therapeutics [39]. Specifically, conventional polymers are rarely stimuli-responsive, do not self-heal, do not degrade in a controlled manner, and are expected to trigger unwanted immune responses, unless thoroughly functionalized.…”
Section: Introductionmentioning
confidence: 99%